Early-life trauma, negative and positive life events, compulsive sexual behavior disorder and risky sexual action tendencies among young women with substance use disorder. (October 2022) - Efrati, Yaniv; Goldman, Keren; Levin, Katya; Rosca, Paola
Highlights: Young women with substance use disorder have higher CSBD and RSB than controls. CSBD was also found to mediate the association between substance use and risky sexual action tendencies. Addictive behaviors were linked with emotional abuse at childhood but not with other types of abuse. Abstract: Although significant advances have been made in the field to date, gender-based issues for women remain a neglected area in much of substance abuse research. In the current study we examined two gaps in the literature: the co-occurrence of compulsive sexual behavior disorder (CSBD) and risky sexual action tendencies among women with substance use disorders (SUDs), and their shared antecedents in the form of early life adversity and negative life events. The sample comprised 132 women of whom 62 had substance use disorder (drug and alcohol) and 70 were healthy controls. Each participant completed self-report measures of drug abuse and alcoholism, compulsive sexual behavior disorder and risky sexual action tendencies as well as early-life trauma and negative and positive life events. Results indicate that young women with substance use disorder have higher compulsive sexual behavior disorder symptoms and more prevalent risky sexual action tendencies than controls. Compulsive sexual behavior was also found to mediate the association between substance use and risky sexual action tendencies. In addition, all addictive behaviors were linked with emotional abuse at childhood but not with other types of abuse. Conversely, negative life events in adulthood were only linked with CSBD and not with substance use. The findings provide deeper insights into the comorbidity of addictive behaviors and an opportunity for developing more effective treatments for women who suffer from these addictions.